0
$\begingroup$

This course page 12-13 (in French) is doing this :

For a low-pass filter, the equation is $$RCy't()+y(t)=x(t)$$ with distributions it's written $$ (-RC\delta'+\delta)*y=x $$ (I don't understand this well, even if I remember a bit the Dirac function and $<\delta, y'>=-<\frac {d\delta}{dx}, y>$ )

Then it is said the solution is $$y(t)=(h*x)(t) \text{, where } h(t)=\frac 1 {RC}e^{-t/RC} Y(t) \text{ (Y is the Heaviside step-function) } $$ (I don't understand how to reach this expression)

$\endgroup$
0
$\begingroup$

The distributional derivative of $h(t)$ is $$h'(t) = \frac{-1}{(RC)^2} e^{-t/RC}Y(t) + \frac{1}{RC}\delta_0 = \frac{-1}{RC}h(t) + \frac{1}{RC}\delta_0$$

You can check this by noticing that for any smooth function $\phi(t)$ with compact support, $$\int_{-\infty}^\infty h(t)\phi'(t)dt = - \int_{-\infty}^\infty \frac{-1}{(RC)^2}e^{-t/RC}Y(t)\phi(t)dt + \frac{1}{RC}\phi(0)$$ (To compute the integral on the left, note that you can change the bounds to $[0, \infty)$ for free, then integrate by parts. The boundary term at $\infty$ is zero since $\phi$ as compact support, and the boundary term at 0 is $\frac{1}{RC}\phi(0)$.)

Remember that the derivative of a convolution can be put on either product, so $$RC(h(t) \star x(t))' = RC\left(\frac{-1}{(RC)^2} e^{-t/RC}Y(t) + \frac{1}{RC}\delta_0\right) \star x(t))$$ so $$RC y'(t) = RC(h(t) \star x(t))' = -(h(t) \star x(t)) + x(t) = -y(t)+x(t)$$ and $$RC y'(t) + y(t) = -y(t)+x(t)+y(t) = x(t)$$ as desired.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.